2016
DOI: 10.1016/j.icarus.2016.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Matching asteroid population characteristics with a model constructed from the YORP-induced rotational fission hypothesis

Abstract: From the results of a comprehensive asteroid population evolution model, we conclude that the YORP-induced rotational fission hypothesis can be consistent with the observed population statistics of small asteroids in the main belt including binaries and contact binaries. The foundation of this model is the asteroid rotation model of Marzari et al. (2011), which incorporates both the YORP effect and collisional evolution. This work adds to that model the rotational fission hypothesis, described in detail within… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 62 publications
(133 reference statements)
0
21
0
2
Order By: Relevance
“…Alternately, these apparent facets may have been caused by higher-velocity impacts and mass loss, such as have affected the asteroids (115), although a heliocentric impact explanation is not consistent with the dearth of large craters on the visible faces of LL and SL, save perhaps for the largest, "Maryland" (8). .=DE F @ A, where w, r, and R are the spin rate, density, and equivalent radius of the asteroid in question, L☉ is the solar luminosity, c is the speed of light, and F = ⨀ 01 − ⨀ ' K is the solar-flux-weighted mean heliocentric distance (77). In the table P is the rotation period, w/(dw/dt) is the spin-rate doubling time, and data sources are indicated.…”
Section: Shape Of Arrokoth's Individual Lobesmentioning
confidence: 68%
See 1 more Smart Citation
“…Alternately, these apparent facets may have been caused by higher-velocity impacts and mass loss, such as have affected the asteroids (115), although a heliocentric impact explanation is not consistent with the dearth of large craters on the visible faces of LL and SL, save perhaps for the largest, "Maryland" (8). .=DE F @ A, where w, r, and R are the spin rate, density, and equivalent radius of the asteroid in question, L☉ is the solar luminosity, c is the speed of light, and F = ⨀ 01 − ⨀ ' K is the solar-flux-weighted mean heliocentric distance (77). In the table P is the rotation period, w/(dw/dt) is the spin-rate doubling time, and data sources are indicated.…”
Section: Shape Of Arrokoth's Individual Lobesmentioning
confidence: 68%
“…Asteroid (1862) Apollo, at 1.5 km across and orbiting at 1.5 au, exhibits the largest, measured YORP coefficient (Y), with an estimated YORP spin doubling time scale of ~5 × 10 5 years for an assumed density of 2500 kg m -3 (Table S1). Accounting for the larger size of Arrokoth, its greater distance from the Sun, and its much lower density (77) lengthens this time scale to 7.5 ×10 9 years. This exceeds the age of the Solar System, and adopting any of the other (lower) Y values in Table S1 would imply even longer time scales for Arrokoth, by up to two orders of magnitude.…”
Section: Binary Merger Mechanismsmentioning
confidence: 99%
“…We have shown that JV6 is a bilobed body, a representative of a class of asteroids called contact binaries. The contact binaries are estimated to make up between 15 and 35% of the NEA population (Benner et al , 2015Jacobson et al 2016). The estimated sizes of the NEA contact-binary population are based on reported radar detections of such asteroids, and not on the results of detailed shape modelling.…”
Section: Discussion and Summary Of Main Conclusionmentioning
confidence: 99%
“…We collected additional light-curve data with associated programmes at the 0.6 m Table Mountain Observatory (TMO) telescope in California (USA) in 2015, and at the 2.5 m Isaac Newton Telescope (INT) in La Palma (Spain) in 2007, and 2016. Close approaches to Earth in 2015, 2016, and 2017 offered an opportunity to observe JV6 with groundbased radar facilities. We observed JV6 as the target of a dedicated Arecibo planetary radar campaign in January 2015, 2016, and 2017.…”
Section: Introductionmentioning
confidence: 99%
“…2000年Rubincam [2] 提出YORP效应是小行星自旋加速的最主要动 力, 给出了YORP力矩的理论公式并实现YORP曲线和 小行星自转状态演化曲线的计算, 在YORP效应的研 究历史中具有里程碑意义. 其后, 有关YORP效应的新 研究成果大量涌现, 包括力矩对地形和质心的高度敏 感性 [6,7] , 小行星碎石堆结构与自转状态耦合变化 [8] , 由YORP加速效应导致的结构演化类型(包括失效 [9] 、 表面滑坡 [10] 、变形 [11] 或分裂 [12] ), 以及双小行星系统 的YORP效应(Binary YORP Effect) [13] 等.…”
Section: 引言unclassified